PELATIHAN BUDIDAYA MAGGOT MENGGUNAKAN SAMPAH ORGANIK DALAM MENINGKATKAN PEREKONOMIAN PEMUDA PUTUS SEKOLAH DI DESA PANNYANGKALANG - Wahda Wahda; Insany Fitri Nurqamar; Shinta Dewi Sugiharti Tikson; Muhammad Rifai; Fatmawati Fatmawati; Sri Ulfa (Yayasan Education and Social Center, 2023)
The accumulation of waste produced by the community, including organic waste, can cause environmental damage. Efforts to deal with organic waste can be made by using it to become maggot food. In maggot cultivation, organic waste is an important element that serves as a food source for maggots. Maggot cultivation has been carried out a lot and has proven to be profitable. Therefore, maggot cultivation training is carried out using organic waste for young people who drop out of school. The aim of this program is to provide knowledge and skills to out-of-school young people so they can carry out maggot cultivation independently and generate income from this cultivation. This training uses 2 methods, namely by providing equipment and direct practice